Peran Guru Pendidikan Agama Islam dalam Pencegahan Perilaku Bullying Siswa melalui Penanaman Nilai-Nilai Akhlak Islami di MTs Miftahus Syafa’ah Indralaya Utara - Indah Salwa; Ikma Mustaqimah; M. Ridho Alfarizi; Muhamad Yudistira Nugraha; Abu Mansur (Journal of Innovative and Creativity, 2025)
Bullying is one of the most prevalent social problems in schools and has a negative impact on students’ development. This study aims to analyze the role of Islamic Religious Education (PAI) teachers in preventing bullying behavior through the inculcation of Islamic moral values at MTs Miftahus Syafa’ah. This research employed a qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that PAI teachers act as educators, mentors, and role models in instilling Islamic morals based on ḥablum minannās (respecting peers, politeness, mutual assistance, refraining from mocking, and avoiding harm). The strategies applied include Islamic education learning, habituation, religious activities, and teacher role modeling. The study also identified several obstacles, such as limited teaching strategies, weak supervision, and the influence of students’ social environment. This research emphasizes that the inculcation of Islamic moral values can serve as an effective preventive strategy against bullying, thereby fostering a religious, harmonious, and conducive school climate.